Clinical manifestations of invasive meningococcal disease in Victoria with the emergence of serogroup W and serogroup Y Neisseria meningitidis. Issue 3 (18th March 2021) - Birrell, Michael T.; Strachan, Janet; Holmes, Natasha E.; Stevens, Kerrie; Howden, Benjamin P.; Franklin, Lucinda J.; Ivan, Mihaela; Kwong, Jason C.
Abstract: Background: Historically, Australian cases of invasive meningococcal disease (IMD) have been most frequently caused by Neisseria meningitidis serogroup B, but recently an increase in cases due to serogroup W (MenW) and serogroup Y (MenY) has occurred. Aim: To determine whether clinical manifestations of IMD have changed due to increased incidence of MenW and MenY. Methods: We performed a retrospective review of IMD cases notified to the Department of Health and Human Services in Victoria, Australia. We compared the period between January 2013 and June 2015 (defined as P1) immediately before the increase in MenW and MenY was noted, with the equal time period of July 2015 to December 2017 (P2), when this increase was observed. Results: IMD was notified more frequently in P2 than P1 (1.24 vs 0.53 per 100 000 person‐years, P < 0.001). IMD cases in P2 were older (46 vs 19 years, P < 0.001), and more likely due to MenW (92/187, 49.2% vs 11/80, 13.8%, P < 0.001) or MenY (31/187, 16.6% vs 4/80, 5.0%, P = 0.01). IMD cases from P2 were more likely bacteraemic (151/187, 80.7% vs 55/80, 68.8%, P = 0.04), while meningitis (68/187, 36.4% vs 41/80, 51.3%, P = 0.03) and rash (65/181, 35.9% vs 45/78, 57.7%, P = 0.002) were less frequent. Intensive care unit admission rates and in‐hospital mortality were unchanged. Conclusion: Alongside an increase in IMD in Victoria, the proliferation of cases of MenW and MenY occurred in older patients, and were more often identified through bacteraemia rather than meningitis or purpura fulminans. Clinicians should be aware of these changes to facilitate earlier identification and treatment of IMD.